Identifying blue ocean leadership items - Noordiana Wan Hanafi, Wan; Daud, Salina; Lyana Baharin, Nur (International Journal of Engineering and Technology, 2018)
The purposes of this paper are to identify the reliability and validity of the blue ocean leadership items. Blue ocean leadership (BOL) focuses on what leaders need to do, not on who they need to be, which is far easier to change and has a direct impact on performance. Stratified sampling is use to select the sample. Data is collected using survey method. Total of 500 questionnaire are distributed to middle to top level manager from the Government Link Companies (GLCs) and Multinational Companies (MNCs). Two type of analysis are used in this study in order to analyze the data which is exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Base from the analysis, 63 items could be used to measure BOL variable. These findings contribute to new knowledge in leadership study.Â Â